ANALISIS TINGKAT KEPUASAN MASYARAKAT TERHADAP MUTU PELAYANAN PUBLIK PADA MASA PANDEMI COVID-19 DI KANTOR BPJS KESEHATAN KABUPATEN BADUNG - Putri, Ayuning Sekar; Listyowati, Rina (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 1 (2022): April 2022DO - 10.24843/ACH.2022.v09.i01.p08, 2022)
The social restriction policy due to the COVID-19 pandemic has had an impact on the delay of various public services, one of which is BPJS Health services. In the midst of a pandemic situation, BPJS Kesehatan is required to provide quality services to the community. Therefore, this study aims to determine the level of community satisfaction in terms of five dimensions of service quality, namely Responsiveness, Reliability, Assurance, Empathy, and Tangible. This study uses a quantitative design with a cross-sectional approach. The sample of this study was 100 people who visited the service office, with the sampling technique using the consecutive sampling method. The results of the univariate analysis show the characteristics of the respondents at the BPJS Kesehatan. The majority of respondents are aged between 26 years and 50 years (62.00%), male and female gender are the same (50.00%), bachelor degree (40.00%), working status Private Employee (49.00%), and domiciled from Mengwi District (29.00%). Bivariate analysis using the Chi-square test found that there was a significant relationship between the five dimensions of service quality and community satisfaction (p-value < 0.001). Most respondents are dissatisfied with the services provided at the BPJS Health Office in Badung Regency, so BPJS needs to pay attention to several dimensions that are still not satisfied by respondents, such as the Tangible aspect, so that the quality of service to the community can continue to be improved during the COVID-19 pandemic. Key word s : Community Satisfaction, Public Services, COVID-19 Pandemic